Output checking - Bär, Andi; Kuin, Irene; Verkooijen, Lona (International Journal of Population Data Science, 2026)
Researchers who conduct research using CBS microdata must have their results to be published checked before they are released outside the secure CBS microdata environment. The output control process has increasingly come under pressure. The risk of errors has increased, because the process was largely manual, the number of datasets to be assessed has grown, and the datasets have become more complex. Moreover, the capacity for checks was limited. This article describes a new application that supports the submission, checking and secure release of results (‘output’) to be published. The new process places more responsibility on the researcher for correctly submitting the output. It is also more efficient and effective in its design. Through this application, the researcher gains immediate insight into compliance with the submission guidelines at the moment of submission, such as the correct file format, and the guidelines to prevent disclosure. For instance, it checks if numbers below 10 are present. There is also a check for encrypted records in the file. Values that have been encrypted within the CBS microdata environment, such as postal codes, must be decrypted before they can leave the CBS. These automated checks make the process more transparent for researchers, make the work of the CBS output controller easier, and reduce the chance of errors.